Evaluation of the Completeness Antenatal Care Coverage (K1-K4) in the Special Region of Yogyakarta Province - Ariningtyas, Ristiana Eka; Yuspita Sari, Rizky; Sevtiyani, Imaniar; Raharjo, Untoro Dwi (Universitas Ibn Khaldun Bogor, 2024)
The case of maternal mortality requires special attention as it serves as a significant indicator for improving health in a country, which is included in the achievement target of Sustainable Development Goals (SDGs) number three, namely Good Health and Well-being. The Maternal Mortality Ratio (MMR) trend from 2016 to 2019 increased and was higher than the set target, whereas in 2020, it decreased below the set target. The high MMR is influenced by many factors, one of which is healthcare services such as Antenatal Care (ANC) examinations for pregnant women. Lack of ANC visits can endanger both the mother and the fetus due to the failure to detect warning signs. Healthcare services in the form of ANC for pregnant women are important to detect signs of pregnancy danger. The aim of this study is to assess the coverage of K1-K4. This research uses a descriptive quantitative method by utilizing secondary data available in the Special Region Of Yogyakarta Kesga Application from 2020 to 2022. The results show that K1 coverage almost reached 100%, and K4 coverage exceeded 80% in the Special Region Of Yogyakarta Province. Healthcare facility access is evenly distributed, and there is a correlation between K4 coverage and the maternal mortality rate, especially for high-risk pregnant women. In conclusion, K1 coverage in the Special Region Of Yogyakarta province has exceeded the national target, while K4 coverage is still below the national target. The high coverage of K1-K4 in Special Region Of Yogyakarta is influenced by many factors, including healthcare facility access.